PEMANFAATAN KOLEKSI REFERENSI DI PERPUSTAKAAN SEKOLAH TINGGI ILMU KOMPUTER INDONESIA (STIKI) DENPASAR - Agastya, I Kadek Ega; Haryanti, Ni Putu Premierita; Resen, Putu Titah Kawitri (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi; Vol 3 No 1 (2023), 2023)
The purpose of this study was to determine the use of reference collections in the Indonesian Computer Science College Library (STIKI). This research was conducted by conducting direct interviews with librarians at the Indonesian Computer Science College Library (STIKI) Denpasar. The data analysis technique used in this study is a data analysis technique with data collection, data reduction, data presentation and the last step is drawing conclusions. Based on the results of research on the use of collections in the STIKI Indonesia Library. Based on the results of the research, the authors show that the users make use of the reference collection very well when there are assignments from the lecturers and do the final assignments. In its use, only a few reference collections are used by users such as Task Reference. The obstacle in the use of reference collections is the lack of understanding of librarian to socialize reference collections in the library. Several other constraining factors are seen in the collections that are not in accordance with the needs of users and the compilation of collections based on artificial classifications, causing some reference collections to be difficult to obtain.